Improvements in co-electrolysis performance and long-term stability of solid oxide electrolysis cells based on ceramic composite cathodes - Yoon, Sung-Eun; Ahn, Jae-Yeong; Kim, Byung-Kook; Park, Jong-Sung (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
The co-electrolysis of CO2 and H2O was performed using a solid oxide electrolysis cell with yttria-stabilized zirconia (YSZ) as the electrolyte and a La0.7Sr0.2Cr0.5Mn0.5O3 (LSCM)-YSZ composite as the cathodic material. The LSCM-YSZ composite cathode showed better co-electrolysis performance than did a La0.7Sr0.3V0.9O3 (LSV)-YSZ composite cathode, suggesting that the catalytic activity of LSCM is higher than that of LSV. After small amounts of CeO2 and Pd had been added as catalysts to the two composite electrodes, the LSCM-YSZ cathode showed better co-electrolysis performance than that of the LSV-YSZ composite electrode. The long-term stability of the co-electrolysis performance of the LSCM-YSZ composite cathode was higher than that of the LSV-YSZ composite cathode. These results show that the electrolysis performance of composite cathodes containing highly active materials such as CeO2 and Pd as catalysts can be improved further by choosing the proper base material. Copyright (C) 2015, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: FUEL PRODUCTION; SOFC ANODES; STEAM; COELECTROLYSIS; HYDROGEN; H2O